2018
DOI: 10.1093/ajcn/nqx023
|View full text |Cite
|
Sign up to set email alerts
|

The effect of consumption temperature on the homeostatic and hedonic responses to glucose ingestion in the hypothalamus and the reward system

Abstract: Background: Excessive consumption of sugar-sweetened beverages (SSBs) has been associated with obesity and related diseases. SSBs are often consumed cold, and both the energy content and temperature might influence the consumption behavior for SSBs. Objective: The main aim of this study was to elucidate whether consumption temperature and energy (i.e., glucose) content modulate homeostatic (hypothalamus) and reward [ventral tegmental area (VTA)] responses. Design: Sixteen healthy men participated in our study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…Further, increased macroscale connectivity, particularly in the prefrontal, parietal, and cingulate cortices is known to be related to eating behaviors in people with obesity (Park et al, 2016; Park, Lee, et al, 2018; Park, Moon, et al, 2018). Indeed, imbalance in inhibitory control and food‐related reward system in the prefrontal cortex and paralimbic areas is associated with increased feelings of hunger (Tataranni et al, 1999; Tataranni & DelParigi, 2003) and may lead to overeating and weight gain (Brooks et al, 2013; Ding et al, 2020; Olivo et al, 2017; Steward, Juaneda‐Seguí, et al, 2019; Steward, Picó‐Pérez, et al, 2019; Vainik, Dagher, Dubé, & Fellows, 2013; Van Meer et al, 2019; Van Opstal et al, 2018; Van Opstal et al, 2019; Verdejo‐Román et al, 2017; Volkow, Wang, Telang, et al, 2008; Ziauddeen et al, 2015). In contrast, we found negative associations with obesity phenotypes in brain regions involved in multisensory processing, particularly precentral gyrus, inferior temporal gyrus, fusiform gyrus, superior temporal sulcus, and thalamus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, increased macroscale connectivity, particularly in the prefrontal, parietal, and cingulate cortices is known to be related to eating behaviors in people with obesity (Park et al, 2016; Park, Lee, et al, 2018; Park, Moon, et al, 2018). Indeed, imbalance in inhibitory control and food‐related reward system in the prefrontal cortex and paralimbic areas is associated with increased feelings of hunger (Tataranni et al, 1999; Tataranni & DelParigi, 2003) and may lead to overeating and weight gain (Brooks et al, 2013; Ding et al, 2020; Olivo et al, 2017; Steward, Juaneda‐Seguí, et al, 2019; Steward, Picó‐Pérez, et al, 2019; Vainik, Dagher, Dubé, & Fellows, 2013; Van Meer et al, 2019; Van Opstal et al, 2018; Van Opstal et al, 2019; Verdejo‐Román et al, 2017; Volkow, Wang, Telang, et al, 2008; Ziauddeen et al, 2015). In contrast, we found negative associations with obesity phenotypes in brain regions involved in multisensory processing, particularly precentral gyrus, inferior temporal gyrus, fusiform gyrus, superior temporal sulcus, and thalamus.…”
Section: Discussionmentioning
confidence: 99%
“…Obesity is thought to be caused by uncontrolled eating, which is highly associated with the imbalance in reward and inhibitory control processing of the brain (Martin et al, 2010; Moore, Sabino, Koob, & Cottone, 2017; Moreno‐Lopez, Contreras‐Rodriguez, Soriano‐Mas, Stamatakis, & Verdejo‐Garcia, 2016; Murray, Tulloch, Gold, & Avena, 2014; Val‐Laillet et al, 2015; Van Opstal, Wijngaarden, Grond, & Pijl, 2019; Verdejo‐Román, Vilar‐López, Navas, Soriano‐Mas, & Verdejo‐García, 2017; Ziauddeen, Alonso‐Alonso, Hill, Kelley, & Khan, 2015). Neurobiological studies have found that dysregulation of reward and inhibitory circuits gives rise to an increased threshold for satiation, ultimately leading to overeating (Martin et al, 2010; Murray et al, 2014; Steward, Miranda‐Olivos, Soriano‐Mas, & Fernández‐Aranda, 2019; Val‐Laillet et al, 2015; Van Opstal et al, 2018; Verdejo‐Román et al, 2017; Ziauddeen et al, 2015). Recent neuroimaging studies have increasingly shown associations between obesity and alterations in cortical and subcortical morphology (Herrmann, Tesar, Beier, Berg, & Warrings, 2019; Marqués‐Iturria et al, 2013; Shott et al, 2015), brain activity (Brooks, Cedernaes, & Schiöth, 2013; Goldstone et al, 2009; Gupta et al, 2018; Opel et al, 2015; Park, Hong, & Park, 2017; Steward, Juaneda‐Seguí, et al, 2019; Stoeckel et al, 2008; Van Meer et al, 2019), functional connectivity (García‐García et al, 2013; García‐García et al, 2015; Lips et al, 2014; Park, Seo, & Park, 2016; Park, Seo, Yi, & Park, 2015), and diffusivity (Gupta et al, 2017; Olivo et al, 2017; Steward, Picó‐Pérez, et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The brain consumes about 20% of glucose derived energy in the human body [10]. The brain responds readily to ingestion of glucose because of its quick absorption [10][11][12], and glucose sensing neurons in the hypothalamus show a homeostatic satiety response almost immediately after ingestion [13][14][15][16][17]. Glucose ingestion has effects on both neuronal activity and functional connectivity throughout the brain in areas involved in reward and feeding behavior [16].…”
Section: Introductionmentioning
confidence: 99%
“…However, because of the complexity and involvement of various brain areas in the regulation of energy balance [33], fMRI investigations of whole brain responses might be more informative for this regulation. Measurements of local BOLD changes, a measure of neuronal activity [34], can be used to analyse the immediate effects of nutrient ingestion on very specific brain areas [13][14][15]35,36], but can also be used to determine whole brain effects on a voxel based level [37]. Analysis of functional connectivity has been used to provide further insights on the network level [16,38].…”
Section: Introductionmentioning
confidence: 99%
“…High BMI is an indicator of obesity, a condition with increasing prevalence worldwide (World Health Organization, 2020) and a critical factor in the development of type 2 diabetes, cardiovascular disease, stroke, cancer, and metabolic syndrome (Jensen et al, 2014;Malik et al, 2013;Raji et al, 2010;Val-Laillet et al, 2015). In addition, multiple neurobiological processes related to obesity have been recognized, including mechanisms regulating eating behaviors, together with genetic and transcriptomic underpinnings (Locke et al, 2015;Martin et al, 2010;Murray et al, 2014;Van Opstal et al, 2018;Steward et al, 2019a;Vainik et al, 2013Vainik et al, , 2018Val-Laillet et al, 2015;Verdejo-Román et al, 2017;Ziauddeen et al, 2015).…”
Section: Introductionmentioning
confidence: 99%